2019
DOI: 10.1002/kjm2.12071
|View full text |Cite
|
Sign up to set email alerts
|

Risks of substance uses, alcohol flush response, Helicobacter pylori infection and upper digestive tract diseases—An endoscopy cross‐sectional study

Abstract: This study examines the effects of environmental hazards, including tobacco, alcohol/alcohol flush response, areca nut, and Helicobacter pylori (H pylori) infection on upper digestive diseases. This is a multi‐hospital‐based endoscopy‐survey cross‐sectional study. Subjects were received upper endoscopies in outpatient clinics at four hospitals in Taiwan between 2008 and 2013. Biopsy‐based methods or urea breath test were used confirm the status of H pylori infection. In total, 8135 subjects were analyzed. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…In addition, we divided the studies according to whether Hp could be confirmed as a present infection, into the present infected subgroup ( Hp positive with rapid urease test, urea breath test, histology, or culture), infection history subgroup ( Hp positive with serological detection, treatment history, or infection history), and not clear subgroup. In the present infected group with 24 studies, the prevalence of Hp infection in BE was significantly lower than that in controls (OR = 0.69; 95% CI, 0.54–0.89; P = 0.005; I 2 = 92%) [ 11 , 13 , 36 , 37 , 39 – 44 , 46 48 , 49 , 51 , 53 , 55 , 56 , 60 63 , 65 67 ], while the negative correlation disappeared again in the infection history subgroup (OR = 0.88; 95% CI, 0.43–1.78; P = 0.73; I 2 = 95%) (Fig. 5 ) [ 12 , 35 , 38 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, we divided the studies according to whether Hp could be confirmed as a present infection, into the present infected subgroup ( Hp positive with rapid urease test, urea breath test, histology, or culture), infection history subgroup ( Hp positive with serological detection, treatment history, or infection history), and not clear subgroup. In the present infected group with 24 studies, the prevalence of Hp infection in BE was significantly lower than that in controls (OR = 0.69; 95% CI, 0.54–0.89; P = 0.005; I 2 = 92%) [ 11 , 13 , 36 , 37 , 39 – 44 , 46 48 , 49 , 51 , 53 , 55 , 56 , 60 63 , 65 67 ], while the negative correlation disappeared again in the infection history subgroup (OR = 0.88; 95% CI, 0.43–1.78; P = 0.73; I 2 = 95%) (Fig. 5 ) [ 12 , 35 , 38 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 62%
“…Subgroup analysis was conducted according to differences in definition of control group. Fourteen studies regarded patients with GERD as control group [ 37 , 43 , 49 , 52 , 54 , 55 , 58 60 62 63 , 64 66 , 67 ]. There was no significant difference in the prevalence of Hp infection between BE and GERD controls (OR = 0.99; 95% CI, 0.82–1.20; P = 0.91; I 2 = 33%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cohort collected information of substance use and history of diseases by standardized questionnaires and a trained interviewer. Patients with history of upper gastrointestinal tract cancer or upper gastrointestinal tract surgery were excluded 13,14 . The gender composition was balanced (50.8% female and 49.2% male) and most participants were 50–69 years of age (48.4%), with (71.2%) having no history of substance use and the percentages of history of cigarette, alcohol and betel quid use were 24.8%, 14.8% and 7.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…O consumo indiscriminado de bebidas alcoólicas, por sua vez, aumenta a predisposição na formação de úlceras gástricas ao estimular a maior liberação de gastrina e consequentemente aumentando a secreção de ácido gástrico (SEYOUM et al, 2020). Chuang et al (2019) constataram que usuários de bebidas alcoólicas apresentaram um risco duas vezes maior de adquirir úlcera gástrica e 1,29 vezes o risco de desenvolverem úlcera duodenal, comparado aos não usuários.…”
Section: Revisão Bibliográficaunclassified